Pengendalian Pengadaan Bahan Baku Sambal Seafood Menggunakan Metode Economic Order Quantity - Eka Aditya Rahman; Wahyudin Wahyudin; Muhammad Rizal Rifa'i (Engineering Faculty at Universitas Singaperbangsa Karawang, 2022)
Entrepreneurs must be considered of procuring raw materials, because it can be a source of considerable expenditure. CV LKM had to incur a large cost for one time procurement of raw materials for each production period, apart from limited access, this was also due to the absence of an appropriate order size, and the exact order schedule. This can affect the quality of raw materials in the form of vegetables because they easily rot or expire. Various methods can be used, one of which is the Economic Order Quantity (EOQ) method, because there are several types of raw materials, the multi-item EOQ method is used. Study aims to determine the order size, order frequency, safety stock, and reorder point (ROP) to produce an efficient cost so that the CV LKM raw material procurement scheduling model is formed. After the calculation, based on the multi-item EOQ method on perishable products, the results were around 3.4 kg and 7.4 kg for order sizes, as well as decreasing order frequency, safety stock of 0.88 kg and 5.77 kg with ROP of 1.4 kg and 6.8 kg. It is also estimated that the total cost to be paid by CV LKM is IDR791.730.